SMART-Valleys: a new participatory approach for land and water management in Benin and Togo - CGIAR Research Program on Rice (2020)
More than 1171 ha (11,000 smallholder farmers cultivate rice) were developed with the Smart-Valleys approach in Benin and Togo. Smart-Valleys increased rice yield by up to 95% and smallholder farmers' income compared to traditional management.